Randomised controlled trial of a web-based programme in sustaining best practice alcohol management practices at community sports clubs: a study protocol. Issue 1 (23rd January 2018) - McFadyen, Tameka; Wolfenden, Luke; Kingsland, Melanie; Tindall, Jennifer; Rowland, Bosco; Sherker, Shauna; Gillham, Karen; Heaton, Rachael; Clinton-McHarg, Tara; Lecathelinais, Christophe; Brooke, Daisy; Wiggers, John
Abstract : Introduction: Community-based interventions have been found to effectively increase the implementation of alcohol management practices and reduce excessive alcohol use and alcohol-related harm at sports clubs. However, once implementation support ceases there may be a reduction in such intervention effects. Thus, ongoing contribution to improving the health of the community is diminished; sustaining practice implementation is a key determinant to address this. One possible solution to the strategic and logistical challenges of sustainability involves the use of the web. The primary aim of this study is to assess the effectiveness of a web-based programme in sustaining the implementation of alcohol management practices by community football clubs. The secondary aim is to assess the effectiveness of the programme in preventing excessive alcohol consumption and alcohol-related harm among members of community football clubs. Methods and analysis: The study will employ a repeat randomised controlled trial design and be conducted in regional and metropolitan areas within two states of Australia. Community level football clubs who are currently accredited with an existing alcohol management programme ('Good Sports') and implementing at least 10 of the 13 core alcohol management practices (eg, not serving alcohol to <18-year-olds) required by the programme will be recruited and randomised to either a web-based sustainability programme or a 'minimal contact' programme. The primary outcome measures are the proportion of football clubs implementing ≥10 of the 13 required alcohol management practices and the mean number of those practices being implemented at 3-year follow-up. Secondary outcomes include: the proportion of club members who report risky drinking at their club, the Alcohol Use Disorder Identification Test (AUDIT) score and mean AUDIT score of club members. Outcome data will be collected via observation at the club during a 1-day visit to a home game, conducted by trained research assistants at baseline and follow-up. Ethics and dissemination: The study was approved by The University of Newcastle Human Research Ethics Committee (reference: H-2013-0429). Study findings will be disseminated widely through peer-reviewed publications and conference presentations. Trial registration number: ACTRN12614000746639; Pre-results .